Efficacy of JAK-JANUS Kinase Inhibitors as Mono Therapy and in Combination with Methotrexate in Active Rheumatoid Arthritis - Wajid, Hamna; Rahman, Fawad; Rana , Zahid Hussain; Azam , Rizwan; Batool, Sidra; Hashmi, Zoha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the efficacyof Janus kinase inhibitors as mono therapy and in combination with methotrexate in patients with active rheumatoid arthritis. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Medicine, Combined Military Hospital, Hospital Multan, Pakistan, from Nov 2022 to Oct 2023. Methodology: A total of 1194 patients aging 18 years or above with active rheumatoid arthritis and taking Tofacitinab (5 mg twice daily) were included in this study. In Group-A patients were continued with oral Tofacitinab (5 mg twice daily) while patients in Group-B were added oral methotrexate (15–25 mg per week). The study’s primary outcome was set as the number of patients achieving ACR50 at 6 months of the treatment. Secondary outcomes were the patients achieving ACR70, low disease activity (SDAI ≤11), remission (SDAI ≤3.3) and response of ≥0.22 in HAQ-D index at 6 months follow up. Results: The Mean±SD of age in this study was 51.66±9.36 years. The female gender was 72.61% of total population while males were 27.39%. The results of the primary outcomes of the study show a statistically significant difference between Group-A and Group-B (39.20% Vs 44.72 respectively, p=0.05) proving the combination therapy to be more effective than monotherapy. Among secondary end points, significantly more patients achieved ACR 70 rate, SDAI ≤11 and SDAI ≤3.3 in Group-B compared to Group-A, however, no statistically significant difference was present regarding achieving ≥0.22 response at HAQ-D index. Conclusion: The combination of a JAK inhibitor with methotrexate is more effective in the treatment of